Affordances of Historic Urban Landscapes: An Ecological Understanding of Human Interaction with the Past - Alves, Susana (European Spatial Research and Policy, 2015)
Heritage has been defined differently in European contexts. Despite differences, a common challenge for historic urban landscape management is the integration of tangible and intangible heritage. Integration demands an active view of perception and human-landscape interaction where intangible values are linked to specific places and meanings are attached to particular cultural practices and socio-spatial organisation. Tangible and intangible values can be examined as part of a system of affordances (potentialities) a place, artefact or cultural practice has to offer. This paper discusses how an ‘affordance analysis’ may serve as a useful tool for the management of historic urban landscapes.